Effects of Muscle Energy Technique with Sustained Natural Apophyseal Glides on Range of Motion in Subjects with mechanical Neck Pain - Nasir Sultan, Kiran Khushnood , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the effect of sustained natural apophyseal glides (SNAGs) along with muscle energy technique (MET) on pain and range of motion in subjects with mechanical neck pain. Methods: This interventional study was carried out at physical therapy department of Kulsum International Hospital, Islamabad from January to May 2017, including 60 participants with mechanical neck pain who fulfilled inclusion criteria and gave written and verbal consent. Subjects were provided with MET and SNAGs thrice a week for 8 weeks. Numeric pain rating scale and inclinometer were used as outcome measures. Data was taken at baseline and after 8 weeks of intervention. Six subjects dropped out and 54 subjects were evaluated at the end of study. Data was analyzed by SPSS v21. Results: There were 26 males and 28 females who participated in study. Pain improved from 7.20+0.91 to 2.75+0.90 with p value .009. Ranges improved as; flexion from 73.53+2.74 to 80.94+4.64 with significance .010, extension from 62.61+2.08 to 67.33+2.20 with significance <.001, right side banding from 32.64+3.36 to 37.88+3.14 with p value <.001, left side bending from 33.00+2.32 to 39.51+2.74 with p value .001, right side rotation from 79.72+2.70 to 86.03+3.27 with p value <.001 and left side bending from 80.05+2.47 to 85.90+3.69 with p value 0.005. Conclusion: SNAGs combined with MET improve range of motion and reduce pain in subjects with mechanical neck pain.